Estimation of total saponin content of commonly available fodder crops for dairy cattle - A. Bharathidhasan; R. Karunakaran; C. Valli; S. Ezhil valavan; T.R. Pugazhenthi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Saponin is one of the important plant secondary metabolite which has been shown to selectively modulate the rumen microbial populations resulting in an improvement of rumen fermentation and decreases the methane production. Chemically saponins are high molecular weight glycosides in which a triterpene saponins or steroidal aglycone moiety is linked to one or more sugar chains. The saponins may be considered a part of plant defense system because they are known to inhibit mould, to be antimicrobial and to protect plants from insect attacks (Francis et al., 2002). Saponin in higher level causes bloat and lower level beneficial for ruminants. The majority of research on saponin has been employed to exploit it for inhibition of rumen ciliate protozoa and selectively inhibiting some bacteria, which might reduces the production of hydrogen ions for the methane emission (Bharathidhasan et al., 2013). Currently numerous studies had been attempted to exploit these saponin as a natural feed additive to modulate the efficiency of rumen fermentation by enhancing protein metabolism, reducing nutritional stress or bloat, decreasing methane emission and improve the animal health and productivity (Patra et al., 2006). Early study has been reported that plants rich in saponins decreased the methane production in the rumen (Agarwal et al., 2006).